Psilochorus simoni (Berland, 1911) (Araneae: Pholcidae), a new record for slovenian spider fauna from Postonjska jama cave - Rok Kostanjšek; Lucija Ramšak (Natura Sloveniae)
An adult female Psilochorus simoni (Berland, 1911) (Pholcidae) was found in Postojna Cave, Slovenia. The species, which originates from subtropical America, has been introduced to Europe where it is generally associated with synanthropic habitats. This is the first record of this rare species in Slovenia and the second from a cave environment in Europe.